Control of flow-generated biofilms with surfactants : evidence of resistance and recovery - Simões, M. (2006)
The action of the cetyltrimethyl ammonium bromide (CTAB) and sodium dodecyl sulfate (SDS), respectively a cationic and an anionic surfactant were investigated to control turbulent and laminar flow-generated biofilms formed by P. fluorescens. The disinfectant action of different concentrations of CTAB and SDS on biofilms was assessed by means of cellular respiratory activity and variation of biofilm mass, immediately, 3, 7 and 12 h after the application of the surfactants. The experiments along 12 h post-surfactant treatment were made in order to assess biofilm recovery. The results showed that, laminar flow-generated biofilms were more susceptible to the action of CTAB than those formed under turbulent flow. Total inactivation of the cells within the biofilms was not achieved for both types of flow-generated biofilms. Concerning SDS, higher concentrations applied promoted significant biofilm inactivation and turbulent and laminar flow had analogous susceptibility to SDS application. CTAB and SDS application did not promote the detachment of biofilms from the surfaces. Post-surfactant action results shown that biofilms recovered its respiratory activity, that in some cases reached higher values than the ones found without chemical treatment. CTAB application promoted similar recovery in the respiratory activity for both biofilms. Turbulent flow-generated biofilms showed a higher potential to recover their metabolic activity than laminar flow-generated biofilms when previously challenged with SDS. Conversely, concerning biofilm mass, any significant variation (increase or decrease) was detected after 12 h of surfactant treatment. This study highlights the need of care in choosing the correct procedure for biofilm control and the influence of hydrodynamic conditions on the persistent and recalcitrant properties of P. fluorescens biofilms.